Supplier Internal Control Quality and the Duration of Customer-Supplier Relationships - Bauer, Andrew M.; Henderson, Darren; Lynch, Daniel P. (The Accounting Review, 2018)
ABSTRACT Internal controls influence information quality, thus affecting the ability of supply chain partners, who rely on collaborative systems of information sharing, to reliably contract. Using SOX-related internal control assessments as a proxy for internal control quality and U.S. GAAP-mandated major customer disclosures, we find that supplier internal control quality influences supply chain relationship duration. Specifically, our evidence demonstrates that: (1) poor internal control quality increases the likelihood of subsequent customer-supplier relationship termination; (2) timely control weakness remediation attenuates termination likelihood; and (3) weaknesses affecting customer contracting drive the effect of internal control quality on relationship termination. Our results control for supplier operational quality and performance, and are robust to propensity score matching techniques, controls for reverse causality, and alternative proxies for relationship termination and internal control quality. Overall, our findings are consistent with customers viewing strong supplier controls as important, albeit overlooked, contracting elements with significant implications for supply chain relationships.